Oleorresina de pinos. Una nueva fuente para la obtención de aditivos químicos - Ada María Casal Viqueira; Elsa Bárbara Martín; Lourdes Gutiérrez; Marino Fonseca; Amado E. Navarro; María T. Valdés; Beatriz Spengler; Susana Guerra (Ciencia Ergo Sum)
This paper presents the results of studies employing Cuban pine oleoresin in its natural state, as a substitute for traditional rosin as raw material for obtaining specific chemical additives. The applications include three varieties of paper sizing, tensides and specialized lubricants. Technical-economical considerations related to the practical introduction of these products also are considered